The State of the World's Children 2011 - Fonds des Nations Unies pour l'enfance (United Nations, 2011)
The State of the World’s Children 2011: Adolescence – An Age of Opportunity examines the global state of adolescents; outlines the challenges they face in health, education, protection and participation; and explores the risks and vulnerabilities of this pivotal stage. The report highlights the singular opportunities that adolescence offers, both for adolescents themselves and for the societies they live in. The accumulated evidence demonstrates that investing in adolescents' second decade is our best hope of breaking the intergenerational cycle of poverty and inequity and of laying the foundation for a more peaceful, tolerant and equitable world.